2023
DOI: 10.3390/membranes13020149
|View full text |Cite
|
Sign up to set email alerts
|

Scaling Up of Steric Exclusion Membrane Chromatography for Lentiviral Vector Purification

Abstract: Lentiviral vectors (LVs) are widely used in clinical trials of gene and cell therapy. Low LV stability incentivizes constant development and the improvement of gentle process steps. Steric exclusion chromatography (SXC) has gained interest in the field of virus purification but scaling up has not yet been addressed. In this study, the scaling up of lentiviral vector purification by SXC with membrane modules was approached. Visualization of the LVs captured on the membrane during SXC showed predominant usage of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…As previously described [18], it can be concluded that 10-20 membrane layers, as often described in the literature [14,[21][22][23], are not required for efficient purification and that the separation takes place in the first membrane layer. The influence of the membrane height on the purification performance is further evaluated in Section 3.3.…”
Section: Impact Of Membrane Pore Size On the Separation Mechanismmentioning
confidence: 69%
See 4 more Smart Citations
“…As previously described [18], it can be concluded that 10-20 membrane layers, as often described in the literature [14,[21][22][23], are not required for efficient purification and that the separation takes place in the first membrane layer. The influence of the membrane height on the purification performance is further evaluated in Section 3.3.…”
Section: Impact Of Membrane Pore Size On the Separation Mechanismmentioning
confidence: 69%
“…Third-generation lentiviral vectors were produced by transient transfection of suspension HEK293T/17 SF cells (ACS-4500, ATCC) with four plasmids in a UniVessel ® 10 L bioreactor operated by a BIOSTAT ® B-DCU (Sartorius, Gottingen, Germany). Detailed information on LV production and nucleic acid digestion can be found in [18]. The cell culture broth was clarified using Sartoclear Dynamics ® Lab V50 (0.45 µm polyethersulfone membrane version) with 5 g•L −1 diatomaceous earth (Sartorius).…”
Section: Lentiviral Vector Production Harvest and Clarificationmentioning
confidence: 99%
See 3 more Smart Citations